Improving the Quality of the Mobile Tax Service Apps in Indonesia: A Delphi Study - Aditya Putra; Reza Fathurrahman (Budapest International Research and Critics University, 2022)
This research aims providing recommendations to improve the service quality of M-Pajak, a mobile-based application developed by the Directorate General of Tax (DGT). M-Pajak was officially launched in June 2021 to simplify and modernize the pre-existing traditional tax services. Eight selected experts participated as persons in this research and exchanged their ideas through a three-round Delphi study carried out from November 2021 to January 2022. The initial release of the application only provides a minimal number of services. Due to limited human resources, the DGT needs a selective development improvement plan for public service apps. This research found that data and information security should be prioritized for future M-Pajak updates.